2011
DOI: 10.1007/s10144-011-0290-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure of the paper waspPolistes olivaceus(Hymenoptera: Vespidae) in Bangladesh

Abstract: Dispersal triggers gene flow, which in turn strongly affects the ensuing genetic population structure of a species. Using nuclear microsatellite loci and mitochondrial DNA (mtDNA), we estimated the genetic population structure of the wasp Polistes olivaceus throughout Bangladesh. The level of population differentiation using nuclear markers (F ST ) appeared to be much lower than that estimated using mtDNA haplotype sequences (A ST ), even after correcting for effective population size differences between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Annotation in this work revealed that late adult lac insects possess the highest numbers of exonic and intergenic SNPs. Furthermore, using microsatellite loci and mitochondrial DNA, researchers in Bangladesh analysed the genetic makeup of the Polistes olivaceous population and found that nuclear markers provided a less accurate indication of the level of differentiation than did mitochondrial DNA haplotype sequencing [40]. Several species have been identified using CO1 which showed that the DNA barcode is a quick and accurate way to identify Korean Vespa species [4].…”
Section: Discussionmentioning
confidence: 99%
“…Annotation in this work revealed that late adult lac insects possess the highest numbers of exonic and intergenic SNPs. Furthermore, using microsatellite loci and mitochondrial DNA, researchers in Bangladesh analysed the genetic makeup of the Polistes olivaceous population and found that nuclear markers provided a less accurate indication of the level of differentiation than did mitochondrial DNA haplotype sequencing [40]. Several species have been identified using CO1 which showed that the DNA barcode is a quick and accurate way to identify Korean Vespa species [4].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an important fraction of the P. biglumis males and females must disperse relatively well and particularly males must be able to cover long distances. Similarly, a major geographic barrier (Jamuna-Padma-Upper Meghna river system in Bangladesh) appears to be a dispersal barrier particularly for females in Polistes olivaceus [75].…”
Section: Spatial Genetic Structurementioning
confidence: 99%
“…Spatial population structure has attracted relatively little attention in paper wasps, but our results in the biglumis-atrimandibularis system are in line with the few existing studies. Significant genetic differentiation has only been found among relatively distant populations (tens to hundreds km apart) [75,76] or across continents [50], but not among nest clusters at local scale e.g., [77][78][79][80][81]. The only earlier genetic study on P. atrimandibularis found marginally significant differentiation among individuals ("races") parasitizing different host species other than P. biglumis, but the study was conducted within a small area in Tuscany and did not study spatial population structure at larger geographic scale [82].…”
Section: Spatial Genetic Structurementioning
confidence: 99%
“…Although the fundamental biology of this species has only recently been examined, a previous genetic study revealed that a Bangladeshi population is divided by the country's widest river system, the Jamuna, Padma, Lower Meghna (JPLM) (Uddin and Tsuchida, 2012). In addition, female philopatry has been observed among populations.…”
Section: Introductionmentioning
confidence: 99%